Efficient T-Cell Compartment in HIV-Positive Patients Receiving Orthotopic Liver Transplant and Immunosuppressive Therapy. (3rd July 2020) - Franceschini, Erica; De Biasi, Sara; Digaetano, Margherita; Bianchini, Elena; Lo Tartaro, Domenico; Gibellini, Lara; Menozzi, Marianna; Zona, Stefano; Tarantino, Giuseppe; Nasi, Milena; Codeluppi, Mauro; Guaraldi, Giovanni; et al.
Abstract: Background: In patients undergoing orthotopic liver transplant (OLT), immunosuppressive treatment is mandatory and infections are leading causes of morbidity/mortality. Thus, it is essential to understand the functionality of cell-mediated immunity after OLT. The aim of the study was to identify changes in T-cell phenotype and polyfunctionality in human immunodeficiency virus–positive (HIV + ) and –negative (HIV – ) patients undergoing immunosuppressive treatment after OLT. Methods: We studied peripheral blood mononuclear cells from 108 subjects divided into 4 groups of 27: HIV + transplanted patients, HIV – transplanted patients, HIV + nontransplanted patients, and healthy subjects. T-cell activation, differentiation, and cytokine production were analyzed by flow cytometry. Results: Median age was 55 years (interquartile range, 52–59 years); the median CD4 count in HIV + patients was 567 cells/mL, and all had undetectable viral load. CD4 + and CD8 + T-cell subpopulations showed different distributions between HIV + and HIV – OLT patients. A cluster representing effector cells expressing PD1 was abundant in HIV – transplanted patients and they were characterized by higher levels of CD4 + T cells able to produce interferon-γ and tumor necrosis factor–α. Conclusions: HIV – transplanted patients have more exhausted or inflammatory T cells compared to HIV + transplanted patients, suggesting that patients who have already experienced a form of immunosuppression due to HIV infection respond differently to anti-rejection therapy.